PELATIHAN IMPLEMENTASI KEWIRAUSAHAAN PADA USAHA MIKRO KECIL, DAN MENENGAH (UMKM) TEH DAN GETUK BU SRI KAWASAN WISATA KEMUNING, KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR - Rohwiyati; Kim Budiwinarto; Juni Trisnowati; Praptiestrini; sulistyo; Yanti Sri Danarwati; Dewi Pujiani; Giarti Slamet (SURAKARTA ABDIMAS JOURNAL, 2023)
ABSTRACT The elaboration of entrepreneurial theory into a practical realm requires serious strengthening and focus, to create people who are truly resilient in running a business. In this description, motivation and providing real examples are needed for business actors, so that they have high motivation to start and develop businesses and open jobs for the community in their environment. The main target in providing business motivation is Tea and Getuk SMEs that have potential prospects for business development, especially looking for food characteristics for Kemuning tourist destinations. This business started from trial and error without being supported by business planning, but over time it has become a promising business, evidenced by a wider market, more and more turnover and the number of employees until now reaches 15 (fifteen) people. Symptoms of significant business development from time to time recommend that business governance with all descendants of tea and getuk business activities cannot survive with the patterns that have been practiced, this is as a result of the development of problems, challenges, especially changes in consumer tastes and business competitors. It is considered necessary to adapt to the completeness of management, information technology, which is able to control the development, challenges and business problems along with the progress of the tea and getuk business. One of the main elements in controlling business development is foresight in reading business situations and problems, in anticipation of the right decisions in order to protect the onslaught of competitors and strengthen business management in the context of business progress, sustainability and sustainability. Keywords: entrepreneurship, tea and getuk business, developing, sustainable.